The Effect of E-Government Information System Implementation on Public Service Quality and Transparency: Case Study at Sei Putih Barat Village - Sirait, Hapipah Zahra; Ayunanda, Windi; Gulto, Eva Ulina; Buqhory , Albar Al; Pasaribu, Elvandry; Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The implementation of an electronic-based government system (e-government) is a strategic effort by the government to improve the quality of public services and government transparency, including at the village level. This study aims to analyze the effect of the implementation of the e-government information system on the quality of public services and transparency in Sei Putih Barat Village. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to village residents as respondents and analyzed using statistical analysis techniques. The data plan used is 60 data. The expected results of this study show that the implementation of e-government information systems has a positive and significant effect on the quality of public services. In addition, the implementation of e-government also has a positive and significant effect on the transparency of village administration. These findings indicate that the optimization of e-government implementation can improve service quality and public information disclosure at the village level. This study is expected to serve as evaluation material for village governments in developing digital-based public services and transparency.